Evaluation of [18F]Favipiravir in Rodents and Nonhuman Primates (NHP) with Positron Emission Tomography - Jian Rong; Chunyu Zhao; Xiaotian Xia; Guocong Li; Ahmed Haider; Huiyi Wei; Jiahui Chen; Zhiwei Xiao; Yinlong Li; Xin Zhou; Hao Xu; Thomas L. Collier; et al. (MDPI AG, 2023)
The COVID-19 pandemic has posed a significant challenge to global public health. In response, the search for specific antiviral drugs that can effectively treat the disease caused by the SARS-CoV-2 virus has become a priority. While significant progress has been made in this regard, much work remains to address this ongoing crisis effectively. Favipiravir is an antiviral drug initially developed for the treatment of influenza and has received approval for emergency use for COVID-19 in many countries. A better understanding of the biodistribution and pharmacokinetics of Favipiravir in vivo would facilitate the development and translation of clinical antiviral drugs for COVID-19. Herein, we report the evaluation of [18F]Favipiravir in naive mice, transgenic mice models of Alzheimer's disease, and nonhuman primates (NHP) with positron emission tomography (PET). The [18F]Favipiravir was obtained in an overall decay-corrected radiochemical yield of 29% with a molar activity of 25 GBq/µmol at the end of synthesis (EOS). PET imaging in naive mice, transgenic mice models of Alzheimer's disease, and nonhuman primates revealed a low initial brain uptake, followed by a slow washout of [18F]Favipiravir in vivo. The [18F]Favipiravir was eliminated by a combination of hepatobiliary and urinary excretion. The low brain uptake was probably attributed to the low lipophilicity and low passive permeability of the drug. We hope this proof-of-concept study will provide a unique feature to study antiviral drugs using their corresponding isotopologues by PET.